Synthesis and Identification of 6,7-Epoxy N,N¢,N¢-Trichloro Derivative of a-Bromocinnamaldehyde Semicarbazone as an Active Decontaminating Agent for Toxic Compounds - Ibomcha Singh, Soram; Prabha, Shashi (Asian Journal of Chemistry, 2013)
An approach was undertaken to synthesize 6,7-epoxy N,N¢,N¢-trichloro-a-bromo-cinnamaldehyde semicarbazone, by the conversion of a-bromo-cinnamaldehyde semicarbazone into its epoxy derivative and then finally the corresponding N-chloramine. Epoxidation was carried out with hydrogen peroxide and then chlorinated using calcium hypochlorite. The reaction between calcium hypochlorite and compounds containing a nitrogen atom with one or more hydrogen atoms attached to it will form chloramines which have lower disinfection efficiency but possess strong decontamination properties against toxic compounds and warfare agents. Their efficacy has to be tested on toxic compounds of phosphorus and CW agents under suitable conditions in sophisticated laboratory.